Islamic Stream Indonesian Wahhabis in a Theological Review - Ulum, Miftachul; Mun'im , Abdul (Annusfy : Journal of Multidisciplinary Research, 2025)
The purpose of this study is to examine the Wahhabi movement in Indonesia from a theological perspective. This research uses a qualitative method with a literature review, through an analysis of primary Wahhabi works and secondary literature examining its development and influence in Indonesia. The results show that Wahhabis emphasize monotheism in three main aspects: rububiyah, uluhiyah, and asma' wa shifat, with a textual approach that differs from the dominant Asy'ariyah and Maturidiyah theologies in Indonesia.